The Relationship Between Self-Esteem and Loneliness Among Indonesian National Armed Forces Retirees - Maula Al Afra; Emmanuel Satyo Yuwono (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
Retirement requires individuals to transition from a structured military environment to a more flexible civilian lifestyle. This change may increase psychological vulnerability, such as lower self-esteem and greater loneliness. This study examines the relationship between self-esteem and loneliness among retired members of the Indonesian National Armed Forces. Using a quantitative correlational design, data were collected from 106 retired personnel of the Indonesian National Armed Forces, selected through purposive sampling. The Self-Liking and Competence Scale–Revised (SLCS-R) and the De Jong Gierveld Loneliness Scale (DJGLS) were used to measure self-esteem and loneliness, and data were analyzed with Pearson Product-Moment correlation. The results show a significant negative relationship between self-esteem and loneliness (r = -0.569; p < 0.05), indicating that higher self-esteem corresponds with lower loneliness. These findings highlight self-esteem as a protective factor in post-service adjustment and emphasize the need for support programs that strengthen self-esteem to help reduce loneliness and promote successful adaptation to civilian life. Keywords: loneliness, retired indonesian national armed forces, retirement, self-esteem